Maqashid Syari’ah Perspektif Imam Haramain al-Juwayni - Ikhsan Nur Rizqi (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2021)
Maqasid Syariah has an important role in finding the rules of law that are not explained in the nash, so that it can provide guidelines and rules of life for human beings in living life. This paper uses a study of literature or literature to reveal how the maqasid Syariah perspective of Imam Haramain al-Juwayni who is known as the previous scholar who first invented the theory of maqasid Syariah. al-Juwayni divides the maqasid of Sharia into two, namely, the maqasid produced from the path of istiqra and the path of ta'aqquli. Then al-Juwayni also divides the maqasid syariah into five categories, namely, dzaruriyyah, hajiyyah, tahsiniyah, Shariah which deals with matters of sunnah and Shariah which are universally reasonable but juz'i or partially which cannot be reasoned. According to al-Juwayni the purpose of the maqasid syariah is to maintain human life that there are four that first maintain the Religion, soul, lineage and property